Disputa teologica in un mondo alla rovescia: il dramma su Abramo di Moshè Zacuto (Altre Modernità, 2011)
Theological controversy in a reversed world;  Moshe Zacuto's drama on Abraham.The foundation of the world (Yessod 'Olam) is believed to be the first Biblical drama written in Hebrew.  It was composed in the first half of the 17th century by the mystical and rabbinical author Moshe Zacuto, who immigrated to Italy from Amsterdam.  In fact the work is mostly based on rabbinic legends about Abraham and his struggle against idolatry, and includes many theological debates between the patriarch and King Nimrod, the pagan tyrant who condemns him to be burnt for his ideas. This paper deals with the ideological background of the drama and the peculiar and paradoxical atmosphere created by the theological debates.  As asserted by several scholars (Berliner, Schirmann. Levy), Zacuto, who was born in a refugees family of  Marrano origin,  alluded in his play to the persecutions of the Jews by the Inquisition in Spain and Portugal. On the other hand, it seems that the play also alludes to 17th Century materialistic philosophy and hedonism, symbolized by the words of Nimrod and his sages.  At any rate, the struggle between Abraham and Nimrod takes place in a highly absurd ideological frame, in which right and wrong are meaningless concepts and true faith is considered as a sort of moral perversion: a reversed world. The paper underlines this hidden and ironic aspect of the play and discusses it, on the basis of some classic works on Carnival reversion, like Cocchiara's Il mondo alla rovescia  and Bakhtin' s Rabelais and his world.
Keywords: Zacuto; Abramo; teatro ebraico; carnevalizzazione